Online breastfeeding publics: Sociality, support and selfies. (August 2022) - Tugwell, Sharon
This article focuses on the practice of breastfeeding selfies, as a relational practice within online breastfeeding groups. I suggest that despite breastfeeding being upheld as the most superior infant feeding method, the practice has a paradoxical relationship to discourses of the "good mother" and the idealisation of motherhood more generally. This is due to the unashamed boldness of the practice, which flies in the face of notions of discretion, with their subsequent links to respectability. Breastfeeding selfies can be understood as gestures for something outside of the mother-infant dyad, therefore insisting on recognising the desire, needs and sociality of the mother. Furthermore, they move to position breastfeeding as a social, rather than an individual or solitary act. The desire for women to share their mothering experiences with other women challenges the individualising notion of the exclusive mother and, furthermore, can be understood as an invitation for intimacy with other women. Whilst the practice has the potential to be interpreted in a way which challenges much of the pernicious "good mother" discourses, it continues to be a practice marked in Whiteness, revealing the inequitable nature of online public spaces.